KOMUNIKASI PENCERITAAN DESTINASI WISATA KOTA LAMA SEMARANG OLEH PEMANDU WISATA SEBAGAI UPAYA BRANDING - Mukaromah; Liya Umaroh (Prosiding Seminar Nasional Terapan Riset Inovatif (SENTRINOV), 2023)
This research is motivated by storytelling activities related to stories about the history of tourist destinations carried out by tour guides as an element of activities in the tourism sector. The purpose of this study was to find out how the use of persuasive communication carried out by tour guides in telling stories related to tourist destinations in the old city of Semarang was associated with branding efforts of a destination to visitors. The method used in this research is a qualitative approach method with the data collection process by conducting observations, and interviews. Observations were made by looking at tourist destinations in the old city of Semarang and conducting interviews with informants of several tour guides. Data is also supported from secondary sources such as references, books or supporting journals. The result is that tour guides in communicating with visitors related to communication activities regarding tourism destinations in the Old City of Semarang carry out the process of communicating with a persuasive approach and in accordance with professional competency standards of tour guides. The diversity of storytelling variations as a tourism commodity that allows it to continue to be developed.